Russian-language adaptation of the international nomenclature of International Consensus on Antinuclear Antibody (ANA) Patterns (ICAP) - O. Yu. Tkachenko; S. V. Lapin; A. V. Mazing; Areg A. Totolian (Медицинская иммунология)
Antinuclear antibodies (ANAs) represent a spectrum of autoantibodies targeted for various nuclear and cytoplasmic components of the cells. Indirect immunofluorescence assay (IIF) is the main detection method for “antinuclear factor”. A positive ANA test is usually reported as a titer and a pattern of fluorescence. The ANA patterns refers to the distribution of staining produced by antibodies that react with antigens located in nucleus and cytoplasm of HEp-2 cells. To standardize nomenclature and descriptions of the various fluorescence patterns of antinuclear factor (ANF), the Initiative of the International Consensus on ANA Patterns (ICAP) group was developed in 2014. The aim of ICAP is to promote consensus regarding nomenclature of ANA patterns, a microphotograph database, as well as classification depending on the employee skills. Information on the main characteristics, as well as specific clinical associations of the patterns is available at www.ANApatterns.org. In ANA classification trees, the patterns are indicated by the #AC (anticell pattern) alphanumeric code, being divided into nuclear, cytoplasmic and mitotic groups. Depending on the clinical significance and/or ease of recognition, this nomenclature focuses on the differences between the patterns described by specialists at competent and expert levels. Of the nuclear types, the most significant are homogeneous, speckled, dense fine-speckled, centromere, nucleolar, nuclear dots. The cytoplasmic types may be discerned into fibrillar, speckled, mitochondrial, Golgi, rods and rings. On leaders, behalf of the ICAP translation team is headed by the Full Member of Russian Academy of Sciences, Professor A.A. Totolian, under the auspices of the Russian Research Society of Immunologists. In this article, we present the Russianlanguage adaptation of the ICAP nomenclature, in order to ensure unification and standardization of ANA detection results in the patients with autoimmune diseases.